PERINTAH DAN LARANGAN DALAM HADITS DITINJAU DARI PERSPEKTIF NORMA ETIKA DAN ETIKET - Haris, Abdul (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The hadiths of the Prophet Muhammad SAW contain teachings that cover many aspects of life, including muamalah (relationships) between fellow human beings. In this muamalah matter, many hadiths mention commands and prohibitions for a Muslim in interacting with other people. In addition, there are also commands and prohibitions related to a Muslim's actions towards himself. Since the early days of Islam, the response of Muslims to what is commanded or prohibited in the hadith has shown differences. On the one hand, there is a group that implements the commands and prohibitions as textual equivalents or based on the apparent meaning indicated by the lafadz (manthuq). This group is then known as ahlu al-hadith. On the other hand, there is a group that understands the text of the commands and prohibitions rationally and does not always practice them textually. This group is known as the ahlu al-ra'yi school. In addition, experts in ushul fiqh also introduced theories about the original meaning of a command or prohibition. There are also those who understand the commands and prohibitions by looking at the context of the Prophet's different positions. This study reviews existing theories related to hadiths containing commands and prohibitions, then at the end tries to apply the terminology of ethics and etiquette to understand these hadiths.